Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1007/bf02637492
|View full text |Cite
|
Sign up to set email alerts
|

Flavor evaluation of copper‐nickel hydrogenated soybean oil and blends with unhydrogenated oil

Abstract: Soybean oils hydrogenated to zero linolenate in the pilot plant with a mixed copper-nickel catalyst and a straight copper chromite catalyst were evaluated and compared for flavor and odor. Hydrogenated oils were winterized and deodorized and stabilized with butylated hydroxytoluene, butylated hydroxyanisole, citric acid, and methyl silicone. Taste panel flavor scores of stored oils and room odor scores of oil at frying temperature were similar for oils hydrogenated either with straight copper chromite or with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…C18:3 ratios. The blending of polyunsaturated oil with more saturated or monosaturated oils is to adjust fatty acid levels to an optimal level, such as combining high-oleic sunflower oil with corn oil or hydrogenated soybean oil with soybean oil [9,10] or combining palm-olein with sunflower oil [11].…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…C18:3 ratios. The blending of polyunsaturated oil with more saturated or monosaturated oils is to adjust fatty acid levels to an optimal level, such as combining high-oleic sunflower oil with corn oil or hydrogenated soybean oil with soybean oil [9,10] or combining palm-olein with sunflower oil [11].…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…Modifying the fatty acid composition of the oil is the most common method used to stabilize the frying oil. Blending polyunsaturated oil with more saturated or monosaturated oils is an option to adjust fatty acid levels to optimal level, such as combining high-oleic sunflower oil with corn oil or hydrogenated soybean oil with soybean oil [9,10] or combining palm-olein with sunflower oil [11]. Previous studies showed that blending of SBO with other oils/fats could improve overall properties [12] as well as oxidative stability.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research at this and other laboratories has provided information concerning the flavor and oxidative stability of soybean oil (1)(2)(3)(4)(5)(6). Early reports established the vital role of citric acid as a metal inactivator (I) and the improved storage stability of soybean oils treated with this additive (2).…”
Section: Introductionmentioning
confidence: 99%
“…Modifying the fatty acid composition of the oil-the most common method to stabilize frying oils-can be done by several methods. For example, blending polyunsaturated oils with more saturated or monounsaturated oils is an option to adjust fatty acid levels to optimal levels, such as combining high-oleic sunflower oil with corn oil or hydrogenated soybean oil with soybean oil (1)(2)(3). Chemically altering the existing fatty acid ratios by hydrogenation increases saturated fatty acids and decreases polyunsaturated fatty acids to produce a more stable oil (3)(4).…”
mentioning
confidence: 98%